2012
DOI: 10.1175/waf-d-11-00020.1
|View full text |Cite
|
Sign up to set email alerts
|

Springtime Fire Weather in Tasmania, Australia: Two Case Studies

Abstract: A number of severe springtime fire weather events have occurred in Tasmania, Australia, in recent years. Two such events are examined here in some detail, in an attempt to understand the mechanisms involved in the events. Both events exhibit strong winds and very low surface dewpoint temperatures. Associated 850-hPa wind-dewpoint depression conditions are extreme in both cases, and evaluation of these quantities against a scale of past occurrences may provide a useful early indicator of future severe events. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The flatter topography of northern and central Australia and less favourable circulation conditions in these regions limits downslope winds, but the Great Dividing Range of the eastern seaboard and mountainous island of Tasmania experience downslope winds at times. While most common in the winter (JJA), westerly winds and downslope flow can occur at any time of year (Sharples et al ., 2010; Fox‐Hughes, 2012). Suitable conditions for downslope winds also occurred over the northern Queensland tablelands, including occasionally as a consequence of tropical cyclones (Ramsay and Leslie, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flatter topography of northern and central Australia and less favourable circulation conditions in these regions limits downslope winds, but the Great Dividing Range of the eastern seaboard and mountainous island of Tasmania experience downslope winds at times. While most common in the winter (JJA), westerly winds and downslope flow can occur at any time of year (Sharples et al ., 2010; Fox‐Hughes, 2012). Suitable conditions for downslope winds also occurred over the northern Queensland tablelands, including occasionally as a consequence of tropical cyclones (Ramsay and Leslie, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of downslope winds to fire potential. Such events not only promote rapid desiccation of fuels, but also strong dry gusty winds facilitate rapid rates of spread of wildfires that pose extreme hazards to communities located downwind and contribute to distinct regional fire regimes (e.g., Westerling et al ., 2004; Fox‐Hughes, 2012; Kolden and Abatzoglou, 2018). Strong downslope winds impose additional impacts on vegetation through windthrow as well as factors related to vegetation growth and establishment (Holtmeier and Broll, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned synoptic patterns are known to produce the most severe fire weather conditions in southeast Australia (e.g., Foley, 1947;Cheney, 1976;Mills, 2005;Fox-Hughes, 2012;Tomašević et al, 2022;Fox-Hughes, 2023). Historical 420 wildfires in Victoria, New South Wales and Tasmania are often related to this particular feature of fire weather -dry summertime cold fronts preceded by noticeable anticyclone (e.g., Reeder and Smith, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The valley periodically funnels strong, hot, northerly winds originating from the center of the Australian continent. These become extremely dry due to the Foehen effect, which is caused by the high plateau in the middle of Tasmania, creating dangerous fire weather [41]. In 1967, such extreme conditions sustained a wildfire that destroyed the outer suburbs of Hobart and threatened the center of the city.…”
Section: Tasmania-reliance On Prescribed Firementioning
confidence: 99%